Analisis Paparan PM2.5 dan PM2.5 serta Karakteristik Individu terhadap Gangguan Fungsi Paru - Nelianis Nelianis; Defriman Djafri; Aria Gusti (Poltekkes Kemenkes Padang, 2025)
Air pollution, particularly exposure to fine particulate matter (PM2.5) and nitrogen dioxide (NO2), is a serious health problem that may impair lung function in high-risk groups such as gas station fuel operators. This study aimed to analyze the relationship between exposure to PM2.5, NO2, and individual characteristics with lung function disorders among gas station workers in Padang City. This research used an analytical descriptive design with a cross-sectional approach, applying environmental health risk analysis (EHRA) and environmental health epidemiology (EHE) methods. A total of 79 respondents from seven gas stations were selected, with data collected through interviews, measurement of PM2.5 and NO2 concentrations, spirometry testing, and assessment of individual characteristics. The findings showed that PM2.5 and NO2 concentrations were below the regulatory threshold; however, 30.4% of workers experienced impaired lung function. Statistical analysis revealed significant associations between lung function and age, gender, and length of employment, whereas pollutant exposure levels, vehicle density, mask use, and smoking status were not significantly associated. It can be concluded that individual characteristics had a stronger influence on lung function disorders compared to direct pollutant exposure. Routine health monitoring, education on the use of personal protective equipment, and work-hour regulation are recommended to reduce health risks among gas station workers.